2022
DOI: 10.1609/icwsm.v16i1.19328
|View full text |Cite
|
Sign up to set email alerts
|

“Rough Day … Need a Hug”: Learning Challenges and Experiences of the Alzheimer’s Disease and Related Dementia Caregivers on Reddit

Abstract: Alzheimer’s disease and related dementia (ADRD) is a collection of disorders involving mental deterioration, which is often quite distressing for the individuals and those caring for them. Online social media platforms have become popular environments for people to share their ADRD caring challenges and experiences. Despite encouraging findings in the literature regarding online support for ADRD caregivers, studies to date have focused only on a single online community about ADRD, which leads to an incomplete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Exclusivity refers to the uniqueness of the most frequent words in a topic, while semantic coherence [27] quantifies the co-occurrence of words in a topic in a general context or all the posts. We assess STM for topic numbers ranging from 5 to 30 and select the optimal number Κ of topics for further analysis [14].…”
Section: Rq2: Association Between Sentiment Changes and Initial Post ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusivity refers to the uniqueness of the most frequent words in a topic, while semantic coherence [27] quantifies the co-occurrence of words in a topic in a general context or all the posts. We assess STM for topic numbers ranging from 5 to 30 and select the optimal number Κ of topics for further analysis [14].…”
Section: Rq2: Association Between Sentiment Changes and Initial Post ...mentioning
confidence: 99%
“…Online social media platforms have emerged as a valuable, convenient resource for caregivers to gain informational and emotional support that may not be easily obtained in traditional offline face-to-face interactions [14,15]. A recent survey indicated that online communities could provide informal caregivers with a sense of understanding, empowerment, support, and belongingness, thus reducing social isolation and improving the emotional wellbeing of these caregivers [16].…”
Section: Introductionmentioning
confidence: 99%
“…Based on internet utilization, informal dementia caregivers can be categorized as (1) non-internet caregivers, who never use the internet; (2) non-online community caregivers, who use the internet but do not participate in online communities; and (3) online community caregivers, who both use the internet and participate in online communities. Current social media-based dementia caregiving research primarily focuses on online community caregivers [25][26][27]. Although improving the online experiences of these caregivers is important [28], understanding how non-online community caregivers perceive the value of online peer support is significant as well.…”
Section: Introductionmentioning
confidence: 99%
“…The integration of the internet into daily life has enabled caregivers to increasingly discuss health-related topics on online platforms [ 20 ], including Twitter [ 24 ], Facebook [ 25 ], and other online communities [ 26 ]. In recent research, higher emotional stress and financial hardship of caregivers were found to be the most significant emerging factors associated with increased health-related internet use [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various machine learning algorithms have been developed to extract relevant information from massive, noisy online data to facilitate biomedical research [ 36 ], including, but not limited to, predicting mental health status [ 37 ], disseminating study information during the COVID-19 pandemic [ 38 ], and learning the needs of patients with ovarian cancer and their caregivers [ 39 ]. However, most studies in the ADRD caregiving field have either identified online ADRD caregiving discussions [ 26 ] or summarized caregiving challenges [ 35 ]. Few studies have differentiated caregivers’ relationships with persons living with dementia.…”
Section: Introductionmentioning
confidence: 99%